Telegram Bot as a Digital Learning Platform in English Language Teaching and Learning - Dewinta Mandalika; Fadhilah Ramadhanty; Dasuki Dasuki; Muchlas Suseno (Universitas Muhammadiyah Semarang, 2023)
Transformation of digital technologies in education has become increasingly popular in recent years. Language teaching has seen a surge in digital learning tools and platforms that offer new and innovative ways of teaching and learning. This study focuses on the use of telegram bot platform in English language teaching and learning activity, as well as many benefits that learners can obtained. A systematic review was employed in this study to investigate the utilization of telegram bot as a digital learning platform in English language teaching and learning by analyzing publication from ERIC and Google Scholar using specific keywords related to the research topic. The search criteria included studies published in English between 2020 to 2023. In total, 10 relevant chosen articles, Preferred Reporting Items for Systematic review, and Meta-Analyses (PRISMA) 2020 guidelines were applied. An inclusion and exclusion criteria selection process were carried out prior to the start of the review to assure the focus of the study. Based on the findings, the articles reviewed claimed that telegram bot platform has various benefits including the effectiveness and advantages in English language teaching and learning. Overall, Telegram bot has the potential to enhance language learning by providing interactive and fun learning experiences. Telegram bot can be a valuable addition to English language teaching and learning practices, teachers and educators can take advantages of telegram bot to provide learners with more beneficial practice to maximize their English skills and knowledge